MANAJEMEN MUTU PEMBELAJARAN DI LEMBAGA PENDIDIKAN ISLAM - Subhan, Moh. (EDUKASI: Jurnal Pendidikan Islam, 2013)
Islamic educational institutions is a form of organization that is held to develop social institutions, both permaen and capricious. This institution has certain patterns in the play function, as well as having its own structure that can bind individuals who are in the shade, so that these institutions have legal force of its own. Quality management is a tool that allows education professionals to adapt to the "forces of change" that bear the education system. Achievement of learning success is not only the responsibility of the student, but the teacher has a responsibility to create a situation that encourages initiative, motivated students to undertake lifelong learning activities.